The Brontë Sisters on Foot: Walking as a Reconfiguration of the Brontë Myth in Sally Wainwright’s BBC Biopic To Walk Invisible - Dinter, Sandra (English Studies, 2020)
This article examines forms and functions of pedestrian movement in Sally Wainwright’s television film To Walk Invisible (BBC, 2016) about the lives of Charlotte, Emily, and Anne Brontë. Proceeding from the premise that walking constitutes a core trope of the Brontë myth, the paper begins with a survey of figurations of walking in the biographies and works of the Brontë sisters, in filmic adaptations of their novels and lives, and in the industry of literary tourism in Haworth. In close readings of selected scenes from the biopic, the article illustrates that Wainwright employs walking as a versatile cinematic tool to characterise the three sisters and to assign to them different concepts of authorship. Furthermore, To Walk Invisible uses pedestrian mobility as a metaphor to critique gender ideologies of Victorian Britain for a contemporary audience and to market the Yorkshire moors as an attractive tourist destination. Finally, walking also features as a self-referential impulse in the film. It allows Wainwright to open a metaperspective on the Brontë myth in British heritage culture to which To Walk Invisible itself contributes as a literary biopic.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Authorship; Brontë country; gender; literary biopic; myth; pedestrian mobility; Sally Wainwright